Rancang Bangun Mesin Replika Penghasil Gas Vulkanik sebagai Studi Awal Monitoring Erupsi Gunung Berapi - umi salamah; Qonitatu Hidayah; Damar Yoga Kusuma (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
Indonesia is one of the countries that has the third-largest number of volcanoes in the world. Several volcanoes are still active today. This places Indonesia prone to disasters from the volcano. One of the volcanic activities is characterized by the release of poisonous gases such as CO2. At a certain threshold, this poisonous gas can kill living things. This research has designed a gas-producing engine as a replica of volcanic gas. This machine is very supportive of the development of volcanic gas research on a laboratory scale because it has the advantage of being lighter, simpler construction, cheaper and portable machine construction process. The gas produced by the machine is tested using the Dragger X-am 7000. , CO2, H2S, SO2, and CO. The results were obtained for 60 seconds of starting the engine, namely CH4 2.0% LEL, CO2 1.6% Vol, H2S 4.3 ppm, SO2 1.0 ppm, and CO 271 ppm.